Finding Usability Bugs with Automated Tests. - HARTY, JULIAN (Communications of the ACM, 2011)
The article discusses automated test methods for finding bugs in computer programs which negatively affect usability. Several ways in which automated tests can help identify problems in web-based applications are described. Automated tests can provide information about the software as it is being developed, helping to quickly identify potential problems. Used as an adjunct to traditional human usability testing, it can offer software developers fast and consistent feedback. Examples of automated testing methods are described.